Empowering widows in Iraq in light of contemporary changes (قضايا سياسية, 2022)
Over the years, Iraq has witnessed many political crises, pressures, changes, and successive and rapid transformations, which affected various aspects of social, economic, intellectual and other life. This led to the emergence of a weak group, (the widow's women), which makes it difficult for her to Control on, family, social and economic life. The two researchers have noticed that widows have recently been living in a state of instability as a result of the many different life struggles they are exposed to, and what is reflected on them in the form of psychological pressures. Difficult crises for them, because their strength and their way of facing the difficulties of life differ from one widow to another, and for this they need help to overcome these psychological, economic and other crises. And because women constitute half of society and To educate the future generations, it was necessary to empower them economically and socially, because this kind of empowerment would in turn lead to their political empowerment.